Optimalisasi Temperatur Sintering Pada Sintered Body Hidroksiapatit Dengan Penambahan Silika Sebagai Material Penguat - Erdinal - Febri; Azisyam Pajri; Ade Indra (Politeknik Negeri Padang, 2023)
Sintered body hydroxyapatite (HA) in the form of pellets has been made by adding silica as a reinforcing material (ratio 60:40 wt.%) by varying the sintering temperature. HA and silica were subjected to a dry mixing process for 2 h, then a wet mixing process was carried out for 2 h with the addition of PVA and alcohol as a binder. The mixing process uses a rotary drum with the addition of zirconia balls with the aim of making the mixture more homogeneous. After the mixing process, the samples were dried for 48 h to remove the alcohol contained. The green body was made using the uniaxial pressing method at a pressure of 100 MPa and held for 3 minutes. The sintering process is carried out variously at temperatures of 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, and 1400°C. with a heating rate of 5ºC/minute and holding time of 4 h. Next, the temperature was lowered to 300ºC with a cooling rate of 5ºC/minute. The results showed that linear shrinkage increased significantly (weight shrinkage increased 12.83% - 25.08% and diameter shrinkage increased 3.26% - 23.21%). The results of the relative density calculation show that there is a significant increase with each variation in sintering temperature, where the increase occurs from 44.4% - 85.6%. The compressive strength value also shows an increase with increasing sintering temperature, namely from 21.2 MPa at 800 oC to 65.9 MPa at 1300 oC. Meanwhile, at a sintering temperature of 1400°C, compressive strength values decreased and oxidation occurred as evidenced by color changes. It can be concluded that the optimization of the sintering process occurs at a temperature of 1300 oC which is proven by the highest compressive strength value and no oxidation occurs.